2017
DOI: 10.1007/s10928-017-9526-0
|View full text |Cite
|
Sign up to set email alerts
|

A two-step deconvolution-analysis-informed population pharmacodynamic modeling approach for drugs targeting pulsatile endogenous compounds

Abstract: Pharmacodynamic modeling of pulsatile endogenous compounds (e.g. growth hormone [GH]) is currently limited to the identification of a low number of pulses. Commonly used pharmacodynamic models are not able to capture the complexity of pulsatile secretion and therefore non-compartmental analyses are performed to extract summary statistics (mean, AUC, Cmax). The aim of this study was to develop a new quantification method that deals with highly variable pulsatile data by using a deconvolution-analysis-informed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The deconvolution model has been applied to these hormones (Johnson, ; [van Esdonk et al. ], ). Thus, this work is more broadly applicable for investigating association hypotheses in these axes as well.…”
Section: Discussionmentioning
confidence: 99%
“…The deconvolution model has been applied to these hormones (Johnson, ; [van Esdonk et al. ], ). Thus, this work is more broadly applicable for investigating association hypotheses in these axes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the used parameters, an individual growth hormone concentration–time profile showed a mean of 7 pulses (range 0–15) during a 14 h timeframe and was highly variable across individuals. The simulated pulse times were included in the dataset as separate columns to be used in NONMEM V7.3 for simulation and parameter estimation [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Having quantified the pulse times a priori reduces the degrees of freedom in the model and enables the quantification of only the remaining parameters required to fit a pulsatile profile, such as the pulse amplitudes, pulse secretion width, and a continuous zero-order (non-pulsatile) endogenous release. Previous publications have shown that this methodology provides an accurate description of the pulsatile data and is capable of quantifying drug effects on highly variable datasets [ 13 , 14 ]. Furthermore, this deconvolution-analysis-informed modelling approach can be used for more realistic clinical trial simulations that mimic the endogenous secretion pattern, in which the high variability from different sources (differences in pulse times, variability in pulse amplitude, variability in the pharmacokinetics, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The pulse frequency, obtained from the deconvolution analysis, of BIM23B065 treated individuals was analyzed for significance (generalized linear model with Poisson distribution, p \ 0.05) compared with the placebo cohort. The pulse frequency and the location of pulses from the deconvolution analysis were converted to a format suitable for population NLME modelling in NONMEM [16,17].…”
Section: Gh Model Developmentmentioning
confidence: 99%
“…Interindividual variability (IIV) in the population parameters and between-occasion variability (BOV) between day 7 and day 12 was included following a bottom-up inclusion procedure. Then, the estimated population parameters and variance distributions were fixed to the placebo estimates and model development continued with the full dataset containing both placebo and BIM23B065 treated individuals [17]. Multiple PK/PD relationships, linear and (sigmoidal) maximal effect (E MAX ), driven by the plasma PK of BIM23B065 or via an effect compartment, were tested for significance on the baseline secretion and pulse amplitude parameters during model development [18].…”
Section: Gh Model Developmentmentioning
confidence: 99%